2021
DOI: 10.1080/00071005.2021.1935711
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Educational Choices in Uncertain Transnational Space: South Asian Diaspora in the United Arab Emirates

Abstract: Transnational higher education (TNHE) has been characterised as a crude form of market-driven internationalisation, often targeting immobile student populations in countries with high demand for international academic degrees. In response to recent scholarship on the role of higher education internationalisation in facilitating and producing diasporic networks, this study examines its inverse: how TNHE services existing diasporic communities in situ by mobilising institutions across borders rather than student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Publication type TNE studies have a high prevalence of non-peer-reviewed gray literature, which oftentimes appears in the form of reports of mixed methods research that was commissioned by government agencies seeking to survey the landscape or provide an update on the TNE context of specific countries or regions (e.g. Knight and McNamara, 2017;Ilieva et al, 2021;Rensimer et al, 2021). Academic research on TNE tends to focus on country-specific, contextualized case studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication type TNE studies have a high prevalence of non-peer-reviewed gray literature, which oftentimes appears in the form of reports of mixed methods research that was commissioned by government agencies seeking to survey the landscape or provide an update on the TNE context of specific countries or regions (e.g. Knight and McNamara, 2017;Ilieva et al, 2021;Rensimer et al, 2021). Academic research on TNE tends to focus on country-specific, contextualized case studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Arp (2016a, b) investigated why TNE students choose postgraduate studies over entering the workforce and found that students were unprepared for applying for work due to a lack of career services. A recent study on international branch campus graduates in the UAE indicates that career services and preparation events are attended by over 75% of students, and this participation is linked to perceived employability gains (Rensimer et al, 2021). In a study of transnational medical school graduates that included a comparison between the home and host campuses (Ireland and Bahrain, respectively), Kassim et al (2016) found that the institution was capable of providing binational career services but that graduates felt the need for a career office that was specific to the transnational career context.…”
Section: Process: Moving Through a Tne Degreementioning
confidence: 99%
“…International branch campuses (IBCs) – operated by international universities for expanding global outreach and student exchange – are now found in some Arab countries. The United Arab Emirates hosts the largest number of IBCs in the Arab world ( Rensimer, 2021 ). It has campuses for international universities such as the University of Birmingham, Heriot-Watt University, the University of South Wales, and the University of Bradford.…”
Section: Current Englishization Policies and Orientations Of Arab Hig...mentioning
confidence: 99%
“…Moreover, offshore campuses function as controlled testbeds for foreign, often Western, forms of education perceived as crucial for a globalised knowledge economy (which scholars have analysed for their complex neo-colonial and imperial implications, see Koch and Vora, 2019). While the more elitist campuses also serve a minority of Arab Gulf citizen students, they mainly offer degree programmes to the large populations of resident migrants to produce a domestic pool of high-skilled labour (Geddie, 2012; Miller-Idriss and Hanauer, 2011; Rensimer, 2021; Stephenson and Rajendram, 2019).…”
Section: Circulation and Containment In The Global Economymentioning
confidence: 99%
“…The latter in particular is an important factor to consider for resident migrants as they live in an insecure and temporary status in the Gulf, and may be forced to leave should they lose employment or the political climate changes. Contrary to the degrees of domestic Emirati or Qatari universities, students believe that the international degrees delivered by offshore campuses provide greater cosmopolitan capital and thus raise not only employment opportunities within their current places of residence but also abroad (Rensimer, 2021). By providing these higher education opportunities to their resident migrant populations, the governments of Qatar and Dubai aim to contain the outflow of potential knowledge workers for international study.…”
Section: Transnational Education Zones: Logics and Mechanisms Of Circ...mentioning
confidence: 99%